Moisture-enabled electricity generation from gradient polyoxometalates-modified sponge-like graphene oxide monolith - Liu, Jia; Qi, Yan; Liu, Dongping; Dong, Dapeng; Liu, Dedi; Li, Zhenghua (Journal of materials science, 2019)
Environmental energy harvesting devices hold great prospect for the next generation electronics, which have attracted intensive attentions recently. In this research, a gradient polyoxometalates-modified graphene oxide (g-POMs-GO) with three-dimensional cross-linking inner structure is synthesized by a weak reductant of GO with ethylenediamine and a special soaking treatment in phosphotungstic acid (HPW). Owing to the gradient introduction of HPW, the as-prepared g-POMs-GO is able to provide moisture-enabled current output of 6.2 uA cm −2 with a power density of ≈ 0.7 mW m −2 by harvesting energy from moisture. Moreover, the humidity-to-electric conversion device of g-POMs-GO provides a new, practical method to track the respiratory activity of subjects and can directly use to record and analyze patterns of human breathing.